Pembangunan Sistem Informasi Pengajuan Proposal dan Laporan Kegiatan berbasis Web Studi Kasus SMAN 1 Giri Banyuwangi - Binti Lukluil Maknunin; Denny Sagita Rusdianto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMA N 1 Giri is one of the senior high schools located on HOS Cokroaminoto 38, Giri, Banyuwangi, East Java with the status of a national standard school. SMA N 1 Giri has several activity organizations and every organization has activities or events that are carried out by submitting activity proposals to get approval from the school. From interviews with SMAN 1 Giri, there are problems that are often faced by both the school and students. The problem in school's side is that some of the parties concerned are difficult to find, because they have high mobility such as the principal, so it is difficult to see in detail the submitted report because of the absence of the relevant softfile, errors in writing or formatting the proposal, and incomplete files due to the absence a template that can be used as a reference for writing proposals and activity reports. As for students, if there are several parties who are not present, students have to wait longer so that if there is a revision or it is rejected, it will be quite a waste of time and paper because students have to resubmit the proposal in hardcopy. To overcome these problems, development is carried out using web technology with the aim of being easily accessible by users. With this system, the author hopes that it can help SMAN 1 Giri in submitting proposals and activity reports. This research uses an Object Oriented approach, namely the OOAD (Object Oriented Analysis and Design) and OOP (Object Oriented Programming) methods. This system has been tested by unit testing and integration testing using the white box testing method, and validation testing using the black box testing method.